PERENCANAAN KONSERVASI SUB DAS CIMUNTUR KABUPATEN CIAMIS - Ajeng Aprilia Romdhon; Kunto Dwi Utomo; Suharyanto Suharyanto; Hari Nugroho (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
The land degradation of Cimuntur Sub Watershed that happened causing the function of sub watershed is changing as a basin. The indication of erosion and sedimentation was 88,55 ton/ha/yr and sediment yield was 0,91 mm/yr. Therefore it needs study to figure out how big is the erotion and sedimentatiom in Cimuntur Sub Watershed so that can get the solution for the problem which happened in Cimuntur Sub Watershed. Analizing of erotion and sedimentation in Cimuntur Watershed is used Universal Soil Loss Equation (USLE) Method and is helped with ArcGIS software. ArcGIS software is used to overlay datas. The input data which is needed for USLE Method is Rain Erosivity Factor (R), Soil Erodibility Factor (K), Slope Length Factor (LS), Land Use Factor (C), and Practical Conservation Factor (P). The result of data overlay by ArcGIS is erotion happened. From the analizing datas is gotten that erotion at Cimuntur Sub Watershed is 963,747 ton/ha/year and sediment yield is 14,649 ton/ha/year. And then making classification of erotion class. This erotion class is made to be used as the consideration base for defining the alternative solution will be done and determine location of erotion and sedimentation solution. The alternative erotion and sedimentation solution of Cimuntur Watershed is done by doing conservation such as vegetative conservation or mechanical conservation. Vegetative conservation can be done by improving the land use management. After doing vegetative conservation, erotion decreases to 237,415 ton/ha/yr and sediment yield 3,61 ton/ha/yr. Whereas mechanical conservation can be done by building a sediment contoller (check dam). Check dam construction is done at big erosion category that is Cirende River with capacity is 8945,95 m3.